The Role of the Dopamine Melanin Pathway in the Ontogeny of Elytral Melanization in Harmonia axyridis - Chen, Xu; Xiao, Da; Du, Xiaoyan; Guo, Xiaojun; Zhang, Fan; Desneux, Nicolas; Zang, Liansheng; Wang, Su (Frontiers in Physiology, 2019)
Polymorphic melanism in insects is a conspicuous phenotype which is derived from specific genotypes, and might be central to speciation processes via assortative sexual selection. At the molecular level, melanism in insects is attributed to the melanin pathway. DOPA decarboxylase (DDC) protein encoded by the DDC gene plays a central role in dopamine-melanin synthesis, the main component of melanin in insects. Although the mechanism of melanism has been elucidated in holometabolous insects, other physiological processes coupled with melanin synthesis are unknown. Herein, we identified DDC from the Asian multi-colored ladybird (Harmonia axyridis), an ideal holometabolous insect for studies of melanization due to highly variable color on their elytra. Analyses revealed that HaDDC (the DDC gene of H. axyridis) was constitutively expressed throughout all developmental stages. We performed RNAi technique to examine the melanin synthesis pathway of elytra in H. axyridis. The transcript levels of HaDDC were significantly suppressed after the injection of double-strand RNA of HaDDC (dsHaDDC) at 300ng/ individual in third instar larvae. Silencing HaDDC in third instar larvae did not result in mortality nor significantly affect pupation and eclosion. We further demonstrated that all adults of H. axyridis (forms succinea, spectabilis and conspicua) with HaDDC silenced in third larvae showed abnormal phenotype which emerged as decreased elytra melanin. However, melanin was still observed in other parts of the adults such as head or pronotum. These results demonstrate for the first time that dopamine-derived melanin is the main contributor in elytra melanization in H. axyridis. Additionally, we provide evidence for DDC in regulating fecundity by showing that silencing of HaDDC in third instar larvae significantly reduced female egg-laying and egg hatching. As such, DDC is likely pleiotropic in respect of its role in melanin production and fecundity processes. These findings bring novel insights into melanin production in holometabolous insects, and contribute to the framework on which further studies may be conducted on the mechanism of pigment production and patterning in various types of insect coloration.